Modifying effect of the serum level of brain-derived neurotrophic factor (BDNF) on the association between BDNF methylation and long-term cardiovascular outcomes in patients with acute coronary syndrome - Choi, Wonsuk; Kang, Hee-Ju; Kim, Ju-Wan; Kim, Hee Kyung; Kang, Ho-Cheol; Kim, Sung-Wan; Kim, Jung-Chul; Ahn, Youngkeun; Jeong, Myung Ho; Kim, Jae-Min (Frontiers in Cardiovascular Medicine, 2023)
Introduction: This study investigated the potential modifying effects of the serum brain-derived neurotrophic factor (sBDNF) level on the association between BDNF methylation status and long-term cardiovascular outcomes in acute coronary syndrome (ACS) patients. Methods: From 2006 to 2012, hospitalized ACS patients were consecutively recruited. The sBDNF level and BDNF methylation status were assessed at baseline in 969 patients who were followed up for major adverse cardiac events (MACEs) over 5–12 years, until 2017 or death. Cox proportional hazards models were utilized to compare the time to first composite or individual MACEs between individuals with lower and those with higher average BDNF methylation levels in the low and high sBDNF groups, respectively. The modifying effects of the sBDNF and average BDNF methylation levels on first composite and individual MACEs were analyzed using Cox proportional hazards models after adjusting for potential covariates. Results: In the low sBDNF group, a higher average BDNF methylation level was linked to an increase in composite MACEs independent of confounding variables, but not in the high sBDNF group (HR (95 percent CI) = 1.04 (0.76-1.44)). The interaction effect between the sBDNF and average BDNF methylation levels on composite MACEs was significant after adjusting for covariates (P = 0.008). Conclusion: Combining the BDNF methylation status and sBDNF levels may help identify ACS patients who are likely to have unfavorable clinical outcomes.